Artificial intelligence ethics: ethical consideration and regulations from theory to practice - Ibrahim, Shurooq Mnawer; Alshraideh, Mohammad; Leiner, Martin; AlDajani, Iyad Muhsen; Bettaz, Ouarda (Institute of Advanced Engineering and Science, 2024)
The advancement of artificial intelligence (AI) has led to its widespread use in sectors such as finance, healthcare, military, and employment in developed countries. However, this reliance has raised concerns about AI governance, particularly regarding algorithmic biases based on skin color, gender, race, and age. Consequently, many countries have introduced regulations and ethical frameworks to address these issues. The Ministry of Digital Economy and Entrepreneurship in Jordan has included AI in its 2022 plan, signaling significant progress. The integration of AI in education programs underscores this commitment. However, addressing AI's potential negative impacts is essential. We propose ethical considerations and regulations for AI to complement Jordan's initiatives. Our research aims to promote responsible AI usage by developing ethical guidelines in Jordan. It presents techniques to identify and mitigate biases related to skin color, gender, and age in AI outputs and datasets. The research includes extensive testing on datasets, analyzing approximately 100 images, and revealing notable error rates, including a 16% error rate in detecting skin color, a 4% error rate in seeing white faces, and a 6% error rate in identifying females over men. Therefore, ethical considerations and regulations for AI applications in Jordan must be implemented.